Impending Regeneration Failure of the IUCN Vulnerable Borneo Ironwood (Eusideroxylon zwageri). (January 2019) - Qie, Lan; Elsy, Alexander D.; Stumvoll, Ashley; Kwasnicka, Magdalena; Peel, Anna L.; Sullivan, Joseph A.; Ettinger, Maisie S.; Robertson, Alasdair J.; Brisbane, Jeanelle K.; Sawyer, Amber L.; Lui, Yan N.; Ngim Ow, Siew; et al.
The regeneration of many climax species in tropical forest critically depends on adequate seed dispersal and seedling establishment. Here, we report the decreased abundance and increased spatial aggregation of younger trees of the Borneo ironwood ( Eusideroxylon zwageri ) in a protected forest in Sabah Malaysia. We observed a high level of seedling herbivory with strong density dependence, likely exacerbated by local aggregation and contributing to the progressively shrinking size distribution. We also note the largely undocumented selective herbivory by sambar deer on E. zwageri seedlings. This study highlights the combined impact of altered megafauna community on a tree population through interlinked ecological processes and the need for targeted conservation intervention for this iconic tropical tree species.